The influence of corporate governance on CSR - Sommensjö, Alexander (2020)
This study responds to the theoretical gap in the academic literature regarding mechanisms of corporate governance and how it affects companies’ corporate social responsibility-efforts. The study also aims to deepen the understanding of corporate governance and corporate social responsibility-efforts in the insurance sector. To achieve this, the study adopts a qualitative approach combined with a multiple-case study research design. The data of the study is gathered through semi-structured interviews with representatives for three companies in the Swedish insurance sector. The concepts of triple bottom line, empowerment and management control systems create the conceptual framework that is used to analyse the data.